Pengaruh Etos Kerja, Kompetensi Sumber Daya Manusia dan Kinerja terhadap Produktivitas pada Kelompok Tani Maju Jaya Desa Bintan Buyu - Sudirman Putra Sirimai; Indra Firdiyansyah; Roni Kurniawan (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
This study examines the influence of work ethic, human resource competence, and performance on productivity at the Maju Jaya Farmer Group in Bintan Buyu Village. The research employed a quantitative approach with a saturated sampling technique involving 39 respondents. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with SPSS 24. The results indicate that work ethic significantly and positively affects productivity (t=3.638, sig=0.001), human resource competence significantly and positively affects productivity (t=2.181, sig=0.036), and performance significantly and positively affects productivity (t=2.737, sig=0.010). Simultaneously, the three variables have a significant positive effect on productivity (F=163.762, sig=0.000) with a contribution of 93.3% (Adjusted R²=0.928). This study confirms that internal factors of farmer group members play a crucial role in improving agricultural productivity in island regions with limited land resources